(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2013)
The changes of subterranean water composition were monitored to estimate the creation and evolution of deformations and settlings in Voghjaberd’s landslide field. Chemical formations were found in the water compounds, which evidenced the existence of deeper biochemical erosion, gas-hydrodynamic pressure, which directly are connected with deformations and settlings.